What worries first‐year students? Psychometric properties of the Student Worry Scale - Fam, Jia Yuin *; Sri Bala Murugan, G.N. *; Yap, Caroline Y. L. * (Wiley, 2020)
The transition to university can be stressful for first-year university students. Despite the fact where the feeling of worry is a shared symptom by various mental health issues, there is a lack of studies that investigate into this matter. As worry is a domain-specific construct, there is a need for a valid and reliable measure of worry specifically for university students. Hence, this study aimed to evaluate the psychometric properties of the Student Worry Scale (SWS), particularly in terms of its validity and reliability. For this purpose, the current study recruited a sample of 295 first-year students to evaluate the psychometric properties of SWS. Exploratory factor analysis yielded a five-factor structure of SWS, which explained 55.7% of the total variance. The yielded five factors were general worries, financial-related concerns, significant other’s well-being, academic concerns, and social adequacy concerns. Inter-correlations between the five factors were all significant (r ranged between .395 and .625). The SWS demonstrated good internal consistency in this study (Cronbach’s α ranged between .786 and .941). Overall, the SWS is psychometrically evidenced to be a reliable and valid content-based worry measure specifically for university students.